MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II MELALUI METODE FONETIK DI SD NEGERI TEGALREJO III - Vika Farida; Heru Purnomo; Muhardila Fauziah (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to improve the early reading skills of second grade students of Tegalrejo III Elementary School through the application of the phonetic method. The problem underlying this study is the weak early reading skills of students in lower grades, which is evident from the inability to recognize letters of the alphabet, arrange syllables correctly, and read words without stuttering. The phonetic method was chosen because it emphasizes the introduction of letter sounds systematically and gradually, with the help of visual media such as pictures to associate letter symbols with concrete meanings. This study is a Classroom Action Research (CAR) with the Kemmis and McTaggart model which includes four stages, namely: planning, implementing actions, observation, and reflection. Each stage is carried out sequentially and continuously to improve the learning process. This study involved 27 students in class 2A. The instruments used were observations to record learning activities and tests to measure students' early reading skills. The phonetic method directly helps lower grade students master the basics of reading, such as letter recognition and syllable arrangement, so that their reading results improve significantly. In cycle I, the average achievement of student abilities reached 78% with the category